HUBUNGAN ANTARA AKTIFITAS FISIK DENGAN KADAR ASAM URAT (GOUT) PADA LANSIA DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM - Ditte Ayu Suntara; Afif D Alba; Mardalisa Hutagalung (Sekolah Tinggi Pariwisata Mataram, 2022)
The prevalence of gout in the population in America based on the National Health and Nutrition Examination Survey (NHANES) 2007-2010 is equal to 3.9% (8.3 million). Gout is estimated to occur in 840 people out of every 100,000 people in Indonesia. Batam City has elderly people with gout as much as 4133 and most of them are in Puskesmas Batu Aji as many as 615 cases. The accumulation of uric acid levels one of which is caused by physical activity. The condition of physical activity in the elderly in Indonesia was obtained by 42% of the elderly with mild physical activity, 37% of the elderly with moderate physical activity, and 21% had severe physical activity. This study aims to determine the relationship between physical activity and levels of uric acid (gout) in the elderly. This type of research is an observational study with cross sectional design. The population in this study were all elderly who suffer from gout in the working area of the Puskesmas Batu Aji in Batam. The sampling technique used in this study was purposive sampling of 61 elderly. The results of this study found that most of the elderly experienced high uric acid levels in heavy physical activity as many as 25 elderly (41.0%). From the chi square statistical test results obtained that the value of p value = 0.005 (<0.05) then Ha is accepted, this shows that there is a significant relationship between Physical Activity and Gout Levels in the Elderly in the Working Area of Puskesmas Batu Aji in Batam City 2020. It is hoped that the elderly can reduce strenuous physical activity in order to prevent the buildup of uric acid levels in the elderly